Influence of Programmed Physical Training on the Performance of Table Tennis Athletes - Ahady, Muhammad Yan; Simatupang, Ayman Faiz; Naibaho, Sahdiaman; Rafael, Kevin; Pasaribu, Kevin Hans (Journal Coaching Education Sports, 2024)
This study aims to explore the influence of a programmed physical training program on enhancing the performance of table tennis athletes at the local table tennis club level. The study utilizes a quantitative research approach with a case study design. Research participants consist of 30 table tennis athletes from one local table tennis club. Data were collected through physical tests covering measurements of muscle strength, agility, and cardiovascular endurance, as well as direct observation of athlete performance during table tennis training sessions. The results of the study indicate a significant improvement in muscle strength, agility, and cardiovascular endurance of athletes after participating in the programmed physical training program. Regression analysis also confirms a positive relationship between the level of participation in the programmed physical training program and athlete performance improvement. The practical implications of this research are that local table tennis clubs can utilize programmed physical training programs as a strategy to enhance their athletes' performance. However, this study has limitations that need to be considered, including the limited generalizability of the results due to being conducted in only one local table tennis club. Therefore, further research with larger samples and diversification of table tennis clubs is needed to confirm these findings more broadly.